Electrospun lipid-coated medicated nanocomposites for an improved drug sustained-release profile. (15th January 2019) - Hai, Tao; Wan, Xi; Yu, Deng-Guang; Wang, Ke; Yang, Yaoyao; Liu, Zhe-Peng
Abstract: Nanotechnology has been extensively explored for the potential applications in developing materials for sustained drug release. In this study, a modified coaxial electrospinning, characterized by a detachable concentric spinneret, was developed for the fabrication of a new kind of hybrid structural nanomaterials. The hybrid nanofibers consisted of a drug-free thin layer of glycerol monostearate as the shell and a drug-loaded nanocomposite containing berberine hydrochloride and ethylcellulose as the core, which were confirmed by scanning electron microscopic and transmission electron microscopic results. X-ray diffraction analyses suggested that the drug berberine hydrochloride was converted into an amorphous state with the carrier ethylcellulose in the core section. Fourier transform infrared spectra suggested that all the components were compatible. In vitro dissolution tests verified that the structural hybrids can provide an improved drug sustained-release profile than monolithic medicated nanocomposites in terms of initial burst release, sustained-release time and tailing-off time. The mechanism involving the influences of sheath layer on the drug release behaviour was suggested. The reported protocols pave a new way for fabricating lipid–polymer-based functional nanostructures with accurate structure–property–performance relationship and are useful for developing a series of new functional nanomaterials. Graphical abstract: Highlights: A structural fiber with drug-free lipid on the medicated nanocomposite was studied. Unspinnable lipid solution was explored as the sheath working fluid. The lipid-coated fibers could provide an improved drug sustained release profile. Clear structure–property–performance relationship was disclosed.